Bahasa Inggris KONSUMSI SUGAR SWEETENED BEVERAGES MENINGKATKAN RISIKO DIABETES MELLITUS PADA REMAJA DI KOTA BOGOR - Jannah, Amalia Rodhatul; Humayrah, Wardina (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2024)
Adolescents are particularly vulnerable to the adverse health impacts of excessive sugar-sweetened beverage (SSB) consumption, which may increase the risk of developing type 2 diabetes mellitus. This study aimed to analyse the association between SSB consumption and the risk of diabetes mellitus among adolescents. A cross-sectional design was employed, involving 54 high school students from Taruna Andigha Senior High School in Bogor City, selected through purposive sampling. Data were collected using standardized questionnaires and anthropometric measurements. The results showed that 42.6% of participants were at high risk for diabetes mellitus, and 44.4% had high SSB consumption habits. Bivariate analysis revealed a significant association between SSB consumption (p=0.018), body mass index for age (BMI/A) (p=0.045), and waist circumference (p=0.023) with the risk of diabetes mellitus. Adolescents with high SSB intake were 4.583 times more likely to be at high risk compared to those with lower consumption. These findings underscore the need for health education and regulation of sugary beverage consumption among adolescents to reduce their risk of diabetes mellitus